The discussion of teaching and learning styles in mathematics subject : a traditional versus interactive-engagement approach / Roslah Arsad … [et al.] - Arsad, Roslah; Wan Abdul Aziz, Wan Noor Hayatie; Abdul Rahman, Anisah; Md Said, Junaida; Baharun, Norhayati (Universiti Teknologi MARA, Perak, 2018)
Technological advances in education have changed the delivery method in teaching and learning. Students have been exposed to more engaging and interactive delivery methods. These changes can further enhance the students' understanding in a more effective way. There are two types of teaching styles in delivering knowledge; it is by using traditional method or applying active learning approach. This paper analyses the learning and teaching styles of the traditional and interactive engagement approach, and also discusses the advantages and limitations of both methods. Learning mathematics is different from learning reading comprehension subject. Techniques and presentations need to be more effective so that students are able understand and solve problems quickly and effectively. Thus, a discussion on both methods is needed in order to identify which method is suitable to be applied in delivering knowledge to the students.